On the existence of block-diagonal solutions to Lyapunov and H∞ Riccati inequalities - Sootla, A; Zheng, Y; Papachristodoulou, A (Institute of Electrical and Electronics Engineers, 2019)
In this note, we describe sufficient conditions when block-diagonal solutions to Lyapunov and H∞ Riccati inequalities exist. In order to derive our results, we define a new type of comparison systems, which are positive and are computed using the statespace matrices of the original (possibly nonpositive) systems. Computing the comparison system involves only the calculation of H∞ norms of its subsystems. We show that the stability of this comparison system implies the existence of block-diagonal solutions to Lyapunov and Riccati inequalities. Furthermore, our proof is constructive and the overall framework allows the computation of block-diagonal solutions to these matrix inequalities with linear algebra and linear programming. Numerical examples illustrate our theoretical results.